Obravnava bolnika z akutno ledvično odpovedjo ob randomiolizi po fizičnem naporu - Kovačič, Ladislav (Medicinski razgledi, 2000)
The paper reports on a patient who developed acute renal failure as a result of myoglobinuria due to rhabdomyolysis induced by intense physical exertion. The authors present the assessment of patients with acute renal failure, placing special emphasis on urinalysis and biochemical analysis of blood serumand urine used for the determination of various ratios and diagnostic indices. These may help the clinician differentiate between prerenal azotemia and acute tubular necrosis, the most frequent forms of acute renal failure. Next, the characteristic features of rhabdomyolysis, particularly of exertional rhabdomyolysis, are presented.
Keywords: Kidney failure, acute; ledvice; akutna odpoved; Etiology; napor; Therapy; rabdomioliza; Rhabdomyolysis; Diagnosis; zdravljenje; Exertion; Adult; Hemoglobinuria; Urinalysis; Biological markers; Uremia; Nephritis, interstitial; Glomerulonephritis; Urethral obstruction; Ureteral obstruction; Creatinine; Urea; diagnostika